Electroacupuncture Ameliorates Abnormal Defaecation and Regulates Corticotrophin-Releasing Factor in a Rat Model of Stress. Issue 2 (April 2017) - Zhao, Yuxue; Cui, Changxiang; Yu, Xiaochun; Xin, Juanjuan; Lu, Fengyan; Gao, Junhong; Zhu, Bing
Objective: To examine the effect of electroacupuncture (EA) treatment on abnormal defaecation in a rat model of chronic heterotypic stress (CHS) and investigate the underlying mechanisms. Methods: 20 male Sprague-Dawley rats were randomly divided into three groups: normal (n=6), CHS (n=7), and CHS+EA (n=7). Rats in the CHS group and CHS+EA groups received four different types of stressors for 7 days. For rats in the CHS+EA group, EA was applied at ST36 in the bilateral hind legs for 30 min before each stress-loading session. Rats in the normal group did not receive stressors or EA treatment. The faecal pellets of each rat were collected and weighed at a fixed time every day. Protein expression of corticotrophin-releasing factor (CRF) in the hypothalamus and colorectal tissues was measured by Western blotting at the end of the experiment on the 7th day. Results: After 7 consecutive days of CHS, the number of faecal pellets, faecal wet weight, and faecal water content were significantly increased in the CHS group compared with the normal group (p=0.035, p=0.008 and p=0.008, respectively). All three parameters were significantly decreased in CHS+EA versus CHS groups (p=0.030, p=0.011 and p=0.006, respectively). Stress significantly increased CRF expression in both the hypothalamus and colorectal tissues. The excessive CRF responses seen following CHS were significantly suppressed by EA treatment. Conclusions: EA treatment can ameliorate stress loading induced abnormal defaecation in rats and decrease protein expression of CRF centrally (hypothalamus) and peripherally (colorectal tissues), suggesting a potentially therapeutic role for EA in stress-related responses.